Identifikasi Kesulitan Dalam Menyelesaikan Soal Cerita Pokok Bahasan Prisma Dan Limas Siswa Kelas VIII Semester II SMP Negeri 4 Delanggu Tahun Ajaran 2014/2015 - Cahyaningrum, Siti, Drs. Sumardi,M.Si (2015)
This study aimed to identify the difficulties and the causes difficulties that the students in solving the subject of the story prism and pyramid in terms of aspects difficulties in implementing the concept, difficulties in spatial ability, difficulty in communication geometric, difficulties in drawing conclusions. This research is a qualitative descriptive study. Subject research study is a student of SMPN 4 Delanggu class VIII C totaling 25 students. The data collection method used is a method of testing, questionnaires, interviews, observation, and documentation. Data analysis techniques through three grooves of data reduction, data presentation, and conclusion. The results show the percentage of geometrical difficulties in communication by 31% is low, difficulties in spatial ability by 46.4% classified as sufficient, difficulties in implementing the concept of a 17.6% classified as very low, and difficulties in the calculation of 44.8% is quite. Based on the results of the analysis of students' answers, questionnaires, interviews, observation that difficulties in spatial ability is the difficulty most of the student caused disadvantaged students to imagine waking up space in the illustrations, the students had tried and was able to imagine waking up space but is less precise and neat in drawing answer sheets, students are still confused in distinguishing between a pyramid shape with the shape of a prism and a lazy attitude to draw first work on the problems.